Depression, anxiety, stress, and satisfaction with life: Moderating role of interpersonal needs among university students - Ooi, Pei Boon; Khor, Kuan Siew; Tan, Choe Chai; Ong, Derek Lai Teik (Frontiers in Public Health, 2022)
Depression, anxiety, and stress are ranked among the top mental health concerns faced by university students in recent times perpetuated by the proliferation of digitalization. Thus, this study was performed to assess the relationship between depression, anxiety, stress, and satisfaction with life, with interpersonal needs (perceived burdensomeness and thwarted belongingness) as moderators. A cross-sectional study using a convenient sampling method was conducted among 430 Malaysian private university students (Mean aged= 20.73 years; SD = 1.26 years). A self-administered questionnaire comprising the Depression, Anxiety and Stress Scale (DASS-21), Satisfaction with Life Scale, and Interpersonal Needs Questionnaire were used. Students who experienced lower depression and anxiety reported higher satisfaction with life under the influence of low perceived burdensomeness. Perceived burdensomeness, when coupled with depression (β = 0.76, p < 0.01) and anxiety (β = 0.79, p < 0.01), contributed 15.8% of variance in satisfaction with life. Students who experienced stress reported higher satisfaction with life under the influence of high thwarted belongingness (β = 0.73, p < 0.01), contributing 17.3% of the variance in satisfaction with life. For university students who experienced depression and anxiety symptoms, mental health practitioners may need to be cognizant of how to support students' education and management of their perceived burdensomeness perceptions.